Access to advanced-level hospital care: differences in prehospital times calculated using incident locations compared with patients' usual residence. Issue 2 (21st December 2021) - Davie, Gabrielle; Lilley, Rebbecca; de Graaf, Brandon; Dicker, Bridget; Branas, Charles; Ameratunga, Shanthi; Civil, Ian; Reid, Papaarangi; Kool, Bridget
Abstract : Studies estimate that 84% of the USA and New Zealand's (NZ) resident populations have timely access (within 60 min) to advanced-level hospital care. Our aim was to assess whether usual residence (ie, home address) is a suitable proxy for location of injury incidence. In this observational study, injury fatalities registered in NZ's Mortality Collection during 2008–2012 were linked to Coronial files. Estimated access times via emergency medical services were calculated using locations of incident and home. Using incident locations, 73% (n=4445/6104) had timely access to care compared with 77% when using home location. Access calculations using patients' home locations overestimated timely access, especially for those injured in industrial/construction areas (18%; 95% CI 6% to 29%) and from drowning (14%; 95% CI 7% to 22%). When considering timely access to definitive care, using the location of the injury as the origin provides important information for health system planning.